The Prevention Review of Chemicals The Misuse as Chemical Weapons in The Act of Attack In Indonesia - Dewi Sulityowati (Journal Civics and Social Studies, 2023)
In numerous regions of the globe, armed conflicts occur, causing not a few casualties in addition to physical destruction. Weapons of Mass Destruction (WMD) or commonly referred to as weapons of mass destruction have become one of the most dreaded weapons with the emergence of chemical, nuclear, radiological, biological, and explosive weapons. In fact, the use of weapons of mass destruction has been outlawed, but production remains unsupervised, allowing a number of so-called terrorists to use readily available chemical weapons raw materials, such as Triacetone Triperoxide (TATP), to manufacture bombs and the like. In addition, chemical weapons whose circulation in liquid and gas forms is not monitored by the Chemical Weapons Convention (CWC) pose a risk of long-term damage such as permanent burns or diseases that continue to plague victims long after the war has ended. The following events are certainly a threat to national security that can be caused by irresponsible individuals with access to chemicals. Therefore, it is necessary to prevent similar occurrences in order to minimize the damage they cause. Through in-depth interviews and secondary data analysis, this study aims to establish the truth. Consequently, participation from relevant stakeholders is required. Where the threat is an effort, work, activity, or action that is deemed a threat to the security, safety, and resilience of the Unitary State of the Republic of Indonesia and various national interests. The authorities supervise the licensing, purchase, and use of these precursors as detailed below. Therefore, it is necessary to develop a new and unique regulation for precursors circulating in Indonesia.